Development of a piezo actuator-based fatigue testing machine for miniature specimens and validation of size effects on fatigue properties - Miyake Toru; He Lei; Itoh Takamoto; Yamamoto Taiki; Hisaka Chiaki (Journal of the Mechanical Behavior of Materials)
This study presents the development of a piezo actuator-based fatigue testing machine specifically for miniature specimens. The machine’s specifications include a maximum axial load of 1 kN, a maximum frequency of 15 Hz, and overall dimensions of 1,174 mm × 370 mm × 270 mm (height × length × width). Finite element analysis was employed to design two types of specimens with dimensions of 22 mm length, 8 mm width, and 2.2 mm thickness, each having a gauge length of 4 mm and diameters of 1.6 and 1.8 mm. Preliminary testing indicated that fractures initiated in the R-section of the specimen with a 1.8 mm diameter, leading to the selection of the 1.6 mm diameter specimen. To examine the influence of size on fatigue behavior, validation tests were conducted using AISI 304 and AISI 310S. Results indicated that, in the low-cycle fatigue region, size effects were negligible. However, as applied stress amplitude decreased, the fatigue life or fatigue limit of the miniature specimens surpassed that of bulk specimens.